Disparities in efficacy and safety of sodium-glucose cotransporter 2 inhibitor among patients with different extents of renal dysfunction: A systematic review and meta-analysis of randomized controlled trials - Hu, Suiyuan; Lin, Chu; Cai, Xiaoling; Zhu, Xingyun; Lv, Fang; Yang, Wenjia; Ji, Linong (Frontiers in Pharmacology, 2022)
Background The pleiotropic efficacy of SGLT2is in patients with different eGFR levels has not been well understood. This systematic review and meta-analysis assessed the disparities in efficacy and safety of SGLT2i treatment across stratified renal function. Methods We searched four databases from inception to December 2021. We included Randomized controlled trials (RCTs) with reported baseline eGFR levels and absolute changes from baseline in at least one of following outcomes: HbA1c, body weight, blood pressure and eGFR. Continuous outcomes were evaluated as the weighted mean differences (WMDs) and 95% confidence intervals (CIs). Categorical outcomes were evaluated as odds ratios (ORs) and accompanying 95% CIs. Results In total, 86 eligible RCTs were included. SGLT2is produced a substantial benefit in glycemic control, weight and blood pressure reduction even in patients with impaired renal function. HbA1c and weight reductions observed in SGLT2i users were generally parallel with the renal function levels although there was an augmented weight reduction in severe renal dysfunction stratum [HbA1c: -0.49% (-0.58 to -0.39%) for normal renal function, -0.58% (-0.66 to -0.50%) for mild renal function impairment, and -0.22% (-0.35 to -0.09%) for moderate renal function impairment, and -0.13% (-0.67 to 0.42%) for severe renal function impairment (P＜0.001 for subgroup differences) ;weight: -2.12kg (-2.66 to -1.59kg) for normal renal function, -2.06kg (-2.31 to -1.82kg) for mild renal function impairment; -1.23kg (-1.59 to -0.86kg) for moderate renal function impairment; -1.88kg (-3.04 to -0.72kg) for severe renal function impairment (P = 0.002 for subgroup differences)]. However, the blood pressure reduction observed in SGLT2i users was independent of renal function. When compared with placebo, the occurrence of hypoglycemia was more frequent in patients with favorable renal function rather than those with substantial renal dysfunction. Conclusions The HbA1c and body weight reductions observed in SGLT2i users were generally parallel with their baseline eGFR levels while blood pressure reductions in SGLT2i users were independent of their baseline eGFR levels. Consistently, when compared with placebo, the hypoglycemia was more frequent in patients with favorable renal function where the HbA1c reduction was profound.